Al-Shaarawi’s Method of Inference of the Waqf Effects and their Effect on his Interpretation of the Surat Al-Baqara and Aal-Imran as a Model - Obeid, Ali; Mejbel , Mahmoud (Islamic Sciences Journal, 2023)
This research aims to know the method that Al-Shaarawi followed in inferring the endowed effects, by collecting and studying the waqf effects that he inferred in his interpretation of Surat Al-Baqarah and the Aal-Imran , and the effect of these hadiths on his interpretation of the Holy Surah, through practical models. It is known that every scientist has jurisprudence and inferences and he may be wrong; A human being he may be right or he may be wrong, and the interpretation of Al-Shaarawi, despite his fame, did not receive the madern study that suits his fame, and this reason prompted me to study Al-Shaarawi's methodology in inferring the suspended effects and its effect on his interpretation, and I chose Surat Al-Baqarah and Aal- Imran. Because they are the longest surahs of the Holy Qur’an, and the benefit will be greater. I ask Allah to grant success.